Travelling wave solutions and regularity results for nonlinear Newton-Schrodinger systems especially in one dimensions - Iqbal, Muhammad Sajid; İnç, Mustafa; Safdar, Samreen; Tarar, Muhammad Akhtar; Ahmed, Muhammad Ozair; Shahid, Naveed (Springer, 2022)
In this article, the soliton solutions of the Newton Schrodinger system are obtained using the solution steps provided by the Kudryashov method. The solutions have interesting solitary waves behavior having different soliton structures. The fundamental novelty of the article is the existence of the underlying system for the real case where the corresponding a-priori estimates with explicit bounds of the solution length were constructed. The second significant contribution is the simulation for the obtained exact solutions are shown with corresponding physical interpretation.
Keywords: Newton Schrodinger system; Nonlinear Partial Differential Equations; Soliton; Existence; Kudryashov method